EFEKTIVITAS WAKTU PELAKSANAAN (PAGI DAN SIANG HARI) TERHADAP HASIL TES KEBUGARAN JASMANI PADA SISWA FASE C SDN GANDUSARI 2 KABUPATEN BLITAR - Listiani, Sevia; Supriatna (Fakultas Ilmu Keolahragaan Unimed, 2025)
Physical fitness is one of the main aspects in supporting the physical, social and mental development of students at the elementary school level. This study aims to determine the effectiveness of the timing of the Indonesian Student Fitness Test (TKSI) in the morning and afternoon on the physical fitness results of phase C students at SDN 2 Gandusari, Blitar Regency. This study is a quantitative study with a comparative descriptive design. The sample of this study was all 38 Phase C students of SDN 2 Gandusari. The instrument used was TKSI, including tests of coordination, accuracy, abdominal muscle strength, agility, and endurance which were carried out at 07.00–09.00 WIB and 12.00–14.00 WIB. Data were analyzed using descriptive statistics, normality tests, homogeneity tests, and Wilcoxon Signed Rank Test. The results showed that the average scores in the morning and afternoon were: coordination 2.89 and 3.05; accuracy 2.18 and 2.47; abdominal muscle strength 3.21 and 3.31; Agility scores were 4.26 and 4.44; endurance scores were 4.28 and 4.13. The Wilcoxon Signed Rank Test showed no significant difference between morning and afternoon (Asymp. Sig. = 0.098). This study concludes that the TKSI can be implemented flexibly, either in the morning or afternoon, while still considering students' physical and psychological readiness and environmental factors so that test results accurately reflect their fitness levels